Shut out? South East Europe and the EU's New Industrial Policy - Will Bartlett (London School of Economics and Political Science (LSE), European Institute, 2014)
This paper explores the potential role of industrial policy to stimulate post-crisis recovery in South East Europe (SEE). Policy reactions in the region have focused on fiscal consolidation and austerity, while the design of active industrial policies to improve competitiveness has been less in evidence. The paper reviews the experience of industrial policies in the EU and shows how these policies have evolved from vertical to horizontal approaches, and how the latter versions of policy have been transferred to the accession states in SEE. The paper reviews the evolution of industrial policies in eight countries of the region and the impact of these policies on industrial production. It argues that the horizontal industrial policies that have been imposed on SEE countries through conditionality embodied in the EU accession process have left their economies vulnerable to adverse spillovers from the eurozone crisis. It concludes with an assessment of the relevance of industrial policies to economic recovery, and questions whether SEE has been 'shut out' of the 'fresh' vertical industrial policy that has been adopted by the EU in recent years.
Keywords: 330; industrial policy; innovation; competitiveness; European Union; South East Europe